한국 산림의 공익적 가치추정 : 선택실험법을 이용하여 - 유진채 (한국농촌경제연구원, 2010)
The purpose of this study was to evaluate forest public functions by using Choice Experiments(CE). Experts interview, focus groups interview and pilot surveys were implemented for efficiency of experimental design. Nine attributes including eight forest public functions and tax payments were selected to estimate public value of forest in Korea. Attributes were the storage and purification function of water, the reduction of soil erosion, the prevention of landslide, sequestration of CO2, formation of living environment, the recreational function of the forest, ecosystem protection, forest landscape improvement and tax payment. 508 citizens were selected using Stratified Sampling Methods, and surveyed by face-to-face interviews. Implicit prices of the attributive levels have been calculated into monetary value per household. The results showed that most preferable forest public functions were formation of living environment, the storage and purification function of water and sequestration of CO2. Results of this study could be used as useful quantitative information related to sustainable forest management in Korea.
Keywords: 지속가능한 산림경영; 선택실험법; 공익적 가치; sustainable forest management; choice experiments; non-market value